Benefit profile of anticoagulant therapy in sepsis: a nationwide multicentre registry in Japan. Issue 1 (December 2016) - Yamakawa, Kazuma; Umemura, Yutaka; Hayakawa, Mineji; Kudo, Daisuke; Sanui, Masamitsu; Takahashi, Hiroki; Yoshikawa, Yoshiaki; Hamasaki, Toshimitsu; Fujimi, Satoshi
Abstract Background Little evidence supports anticoagulant therapy as effective adjuvant therapy to reduce mortality overall in sepsis. However, several studies suggest that anticoagulant therapy may reduce mortality in specific patients. This study aimed to identify a subset of patients with high benefit profiles for anticoagulant therapy against sepsis. Methods This post hoc subgroup analysis of a nationwide multicentre retrospective registry was conducted in 42 intensive care units in Japan. Consecutive adult patients with sepsis were included. Treatment effects of anticoagulants, e.g. antithrombin, recombinant thrombomodulin, heparin, and protease inhibitors, were evaluated by stratifying patients according to disseminated intravascular coagulation (DIC) and Sequential Organ Failure Assessment (SOFA) score. Intervention effects of anticoagulant therapy on in-hospital mortality and bleeding complications were analysed using Cox regression analysis stratified by propensity scores. Results Participants comprised 2663 consecutive patients with sepsis; 1247 patients received anticoagulants and 1416 received none. After adjustment for imbalances, anticoagulant administration was significantly associated with reduced mortality only in subsets of patients diagnosed with DIC, whereas similar mortality rates were observed in non-DIC subsets with anticoagulant therapy. Favourable associations between anticoagulant therapy and mortality were observed only in the high-risk subset (SOFA score 13–17; adjusted hazard ratio 0.601; 95 % confidence interval 0.451, 0.800) but not in the subsets of patients with sepsis with low to moderate risk. Although the differences were not statistically significant, there was a consistent tendency towards an increase in bleeding-related transfusions in all SOFA score subsets. Conclusions The analysis of this large database indicates anticoagulant therapy may be associated with a survival benefit in patients with sepsis-induced coagulopathy and/or very severe disease. Trial registration University Hospital Medical Information Network Clinical Trial Registry (UMIN-CTR ID:UMIN000012543 ). Registered on 10 December 2013.